Gastric tube pull-up after esophagectomy for cancer - Costa, Paulo (2014)
Introduction: Anastomotic complications are responsible for significant morbidity after oesophagectomy for cancer. Cervical oesophagogastrostomy is associated with high incidence of anastomotic leaks (0 – 18%) and stenosis (1- 43%). The aim of this study was to address the reliability of our method of preparation of the gastric tube, the pull-up of the gastric conduit and the esophagogastrostomy, based on a consecutive series of esophagetomies for cancer. Material and Methods: Retrospective analysis of the last 50 consecutive patients, with oesophageal carcinoma, 7 female and 43 males, median of age 63 [46-85] years. Oesophagocoloplasties were excluded from the group. A gastric tube was pulled-up to the thorax (n=3) or the neck (n=47). Gentle manipulation of the stomach in all the steps of its mobilization, preservation of the gastric vascularization of the tube (details for preserving the right and left gastric vascular  arcades and networks were focused), the technique to carry out the gastric pull-up and the hand-sewn end-to-lateral anastomosis to the posterior face of the tube were key technique details presented. Homeostatic monitoring was guaranteed. Clinical, endoscopic and radiologic control of the anastomosis was done. Endoscopic control of bleeding and stenosis was achieved on demanding cases.Results: 2 anastomotic leaks and 1 detected only on radiologic study. No gastric tube necrosis. 1 haemorrhage endoscopic controlled. 11 cases of post-operative stenosis required one ore more dilatation sessions through the first year. Hospital stays, median – 19 [9-64] days. Mortality: 8 weeks – 8%; in hospital – 14%. Survival median – 17 [3 – 75] months.Conclusions: A reliable preparation of the gastric tube for pulling up is founded on key technique points. Strict adherence to a meticulous preservation of the gastric tube vascularization is mandatory for minimizing complications. Control of the homeostasis during the operative procedure and in the post-operative period was a significant issue in our experience. Early diagnosis and fixing of complication is crucial for getting good results.Keywords: gastric tube, gastric tube pull-up, cervical oesophagogastrostomy